An investigation into teachers’ classroom language in english class at high schools in da nang city - Lê,Thị Tuyết Mai (2016)
This study aims at conducting the linguistic features of classroom language used by teachers in English lectures at high schools in Da Nang City in terms of syntax, semantics and pragmatics. The theoretical background of speech acts, discourse analysis and functional grammar are used as the framework for analysis. Both qualitative and quantitative were applied to the data collection and data analysis. Data used for the study was collected from the recordings of English lectures at some high schools in Da Nang city and the questionnaires. Informants of thesis were ninety four teachers of English from some high schools in Da Nang City. The first part of the analysis was to discover the features of language that teachers used in English class according to five discourse moves in classroom. In each moves, the structures of different types of sentences as well as theirs meaning functions were analyzed. The second part was to discuss about some reasons leading to teachers‟ difficulties in using English in lectures. The study found that teachers used different kinds of sentences including declarative, imperative, interrogative and exclamative in each move of the lesson to express various speech functions such as statement, command, question and offer. What is more, syntactic elements in Mood/Residue structure also showed different functions in each kind of sentence. Hopefully, the research results can help teachers and language learners get some experiences to teach and learn language effectively.